Pengembangan dan Pemasaran Potensi Beras Menor di Desa Wijimulyo Kapanewon Nanggulan, Kabupaten Kulon Progo - Dharomesz, Vonezyo Yupanzara (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2023)
Community Service Program is a compulsory program from Atma Jaya Yogyakarta University which is carried out as a form of dedication by students to the community. Wijimulyo village located in Nanggulan District, Kulon Progo Regency, Special Region of Yogyakarta is an area that will be developed by the 120 group. Wijimulyo village has variety potency, start from the tourism until the agriculture and the 120 group wants to develop the agriculture potency which is about the menor rice. Menor rice is an under-development rice in the Kulon Progo Regency. The drawback of this rice is that it has just been registered to the Ministry of Agriculture, so it still not well known by the public of Wijimulyo village. Because of that drawback, the 120 group of Community Service Program wants to develop that potency by doing a marketing about menor rice’s product so that menor rice can be more known by the public of Nanggulan District and known nationally as well.